2016
DOI: 10.1021/acs.energyfuels.5b02029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selective Catalytic Reduction System on Fine Particle Emission Characteristics

Abstract: Based on commercial catalysts (V 2 O 5 −WO 3 /TiO 2 ), the effects of a selective catalytic reduction (SCR) system on the emission characteristics of fine particles were investigated. The size distribution, morphology, element compositions, and chemical compositions of fine particles at the outlet of the SCR system were measured by an electrical low pressure impactor (ELPI), particulate matter (PM 10 /PM 2.5 ) samplers, field emission scanning electron microscopy/energy dispersive spectrometry (FSEM−EDS), X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Some studies showed an increase in the nonvolatile PN emissions due to secondary formation of nanoparticles in the SCR system (Czerwinski et al 2015). These particles could be nitrates and sulfates (Amanatidis et al 2014;Bao et al 2016). Thermogravimetric analysis showed that a part of ammonium sulfate and ammonium bisulfate still exists as nonvolatile (solid) particles within the optimal temperature range (300-400 C) of the SCR process, which is also the temperature of the volatile particle removers of the PN systems (Bao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed an increase in the nonvolatile PN emissions due to secondary formation of nanoparticles in the SCR system (Czerwinski et al 2015). These particles could be nitrates and sulfates (Amanatidis et al 2014;Bao et al 2016). Thermogravimetric analysis showed that a part of ammonium sulfate and ammonium bisulfate still exists as nonvolatile (solid) particles within the optimal temperature range (300-400 C) of the SCR process, which is also the temperature of the volatile particle removers of the PN systems (Bao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These particles could be nitrates and sulfates (Amanatidis et al 2014;Bao et al 2016). Thermogravimetric analysis showed that a part of ammonium sulfate and ammonium bisulfate still exists as nonvolatile (solid) particles within the optimal temperature range (300-400 C) of the SCR process, which is also the temperature of the volatile particle removers of the PN systems (Bao et al 2016). Others have also assumed that these nanoparticles originate from isocyanic acid polymerization, urea pyrolysis and urea micro-explosions (Lee et al 2007;Robinson et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The type of the prepared catalyst samples was ZERONOX1831K, and the catalyst parameters are listed in Table 1. The catalyst adopts TiO 2 as the carrier, and the main active ingredients are V 2 O 5 , WO 3 , and MoO 3 . The fresh and deactivated catalysts were labeled as C and C0, respectively.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…SO 2 , SO 3 , fly ash, and alkali metals contained in the flue gas may decrease the denitrification capacity of the catalyst. SO 3 reacts with NH 3 to form (NH 4 ) 2 SO 4 [2], NH 4 HSO 4 [3], and CaSO 4 [4]. These small particles, with a particle size <10 µm [5], with sticky ammonium sulfate particles, especially ammonium bisulfate, may clog the micropores of the catalyst surface [6,7] and stain and corrode the downstream devices of the SCR, such as the air preheater [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation